Improving Critical Thinking Skills Through Problem-Based Learning Assited by Youtube for Class XI IPS Students of SMAN 1 West Sumatra - Hermana, Rina (LANGGAM: International Journal of Social Science Education, Art and Culture, 2022)
This research is motivated by the low critical thinking skills of students in sociology learning. Sociology learning does not only emphasize material understanding but forms students' critical thinking skills. This study aims to determine the increase in critical thinking skills of class XI IPS students at SMAN 1 West Sumatra through problem-based learning assisted by YouTube. This type of research is Classroom Action Research (CAR), which consists of two cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The research subjects were students of class XI IPS at SMAN 1 West Sumatra for the 2022/2023 academic year, with a total of 25 students. Data collection techniques used are observation, interviews, and tests. Data were analyzed using qualitative analysis techniques. The results of the study reveal that problem-based learning assisted by YouTube can improve students' critical thinking skills. In the first cycle, all students' critical thinking skills (100%) were in the uncritical criteria and in the second cycle, there was an increase, namely all students (100%) were in the minimum critical criteria. The six indicators of students' critical thinking have increased. The action in cycle I is to give problems to students in the form of orders to analyze YouTube videos about social problems with the YouTube link that has been provided in the LKPD. The actions in cycle II were slightly different from cycle I, namely students were instructed to look for videos of social problems on their own to analyze. The next action is to give rewards to students who experience increased critical thinking skills.